Biosecurity and Biosafety Measures to Control Disease Transmission Between Humans, Animals and Environment - Tabish, Saba; Batool, Fatima; Ahmad, Maqsood; Arslan Azam, Mirza Muhammad; Qurat-ul-Ain; Asadullah; Riaz, Hammad; Muhammad Aqib; Hashmi, Hammad Ahmed; Ahmad, Sohail; Sabir, Anum (Indus Journal of Bioscience Research, 2025)
Biosecurity and biosafety are essential for avoiding and limiting disease transmission among humans, animals, and the environment. Given the rising incidence of zoonotic outbreaks like COVID-19 and avian influenza, it is essential to establish comprehensive frameworks incorporating biosecurity measures across all industries. This study aimed to assess the effectiveness of biosecurity and biosafety protocols in mitigating disease transmission at the human-animal-environment interface. A mixed-methods strategy was employed, incorporating field observations, surveys, environmental sampling, and laboratory analysis at three study sites: live animal markets, livestock farms, and wildlife conservation areas. Statistical and geographic modeling tools were employed to analyze data about compliance rates, contamination levels, and the effects of biosafety interventions. The findings indicated that adherence to biosecurity standards was greatest at livestock farms (75%) and least in live animal markets (45%), with a notable correlation between awareness levels and compliance rates (r = 0.78, p < 0.01). Environmental sampling revealed significant contamination levels in markets, with a pathogen detection rate of 65%. Biosafety protocols, including personal protective equipment and animal isolation, were observed to decrease infection rates by 10% following deployment. Notwithstanding its contributions, the study is constrained by its geographic scope and sample size, potentially impacting the generalizability of its findings. These findings emphasize the necessity of focused interventions, stakeholder education, and comprehensive environmental monitoring to improve biosecurity. Future research must concentrate on broadening study areas, incorporating advanced technologies, and assessing the long-term effects of biosecurity frameworks. This research enhances global health security by offering actionable insights for policy formulation and practical execution.